Heroes of the dawn Celtic myth (Myth and mankind., 1996)
Enter the Celtic world of gods, goddesses, & the cosmos, where King Arthur pulled a sword from a stone. Here, with maps & historical overviews, are some of the most powerful & unforgettable Celtic stories ever told. A dramatic series that captures, culture by culture, the information that never makes it into the history books: strange stories, mystic rites, angry gods, vision quests.